The Oxford handbook of Bayesian econometrics - Geweke, John.; Koop, Gary.; Dijk, Herman K. van. (Oxford : Oxford University Press, 2011)
This handbook is aimed at researchers and policymakers wanting to learn about Bayesian methods in specialized fields, and for graduate students seeking to make the final step from textbook learning to the research frontier. It contains contributions by leading Bayesians on the latest developments in their specific fields of expertise.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Econometric models; Bayesian statistical decision theory